Pengaruh Marketing Mix Terhadap Keputusan Pembelian Konsumen Sayur Hidroponik di Kabupaten Lima Puluh Kota: Pengaruh Marketing Mix Terhadap Keputusan Pembelian Konsumen Sayur Hidroponik di Kabupaten Lima Puluh Kota - Yuliatin attin (UNIVERSITAS LANCANG KUNING, 2022)
Generally vegetable plants are cultivated conventionally, but with the development of knowledge, they finally began to be cultivated with hydroponic technology. One of the efforts to develop a hydroponic business is in terms of marketing by using a marketing tool known as the marketing mix which has a role that has an impact on the quantity of sales and future development of the hydroponic business. The purpose of this study is to identify the variables of the marketing mix that have a simultaneous, partial and dominant effect on the purchase of hydroponic vegetables in Lima Puluh Kota Regency. The research method used is a quantitative method. The method of data collection is by using a closed questionnaire, in which the answers have been provided by. The number of respondents as many as 90 people with purposive sampling method or in accordance with certain criteria. The data analysis technique used is validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination, simultaneous test and partial test. The results of the data that have been processed indicate that the research variables that have no effect on consumer purchasing decisions are the promotion variable (X3) and the place/distribution variable (X4). The variable obtained an increase in the significance value of 0.121 and the place/distribution variable of 0.170. The variables that have an effect are the product variable (X1) and the price variable (X2) because each has a significance value of 0.000 and is also the most dominantly influential variable. Keywords: Hydroponic vegetables, Marketing mix, consumer purchasing decisions